2012
DOI: 10.1111/j.1365-2982.2012.01935.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of gallbladder smooth muscle function is an early feature in the development of cholesterol gallstone disease

Abstract: Background Decreased gallbladder smooth muscle (GBSM) contractility is a hallmark of cholesterol gallstone disease, but the interrelationship between lithogenicity, biliary stasis and inflammation are poorly understood. We studied a mouse model of gallstone disease to evaluate the development of GBSM dysfunction relative to changes in bile composition and the onset of sterile cholecystitis. Methods BALB/cJ mice were fed a lithogenic diet for up to 8 weeks, and tension generated by gallbladder muscle strips w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 48 publications
1
37
0
2
Order By: Relevance
“…A study by Lavoie et al . proved that excess cholesterol in the smooth muscle of the gallbladder attenuates the ability of the muscle to contract as a result of changes in signal transduction and ion channel activity, decoupled membrane receptor–ligand interactions and disturbances in contractile protein activity. Moreover, in a subsequent study on guinea pigs fed a lithogenic diet, Lavoie et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Lavoie et al . proved that excess cholesterol in the smooth muscle of the gallbladder attenuates the ability of the muscle to contract as a result of changes in signal transduction and ion channel activity, decoupled membrane receptor–ligand interactions and disturbances in contractile protein activity. Moreover, in a subsequent study on guinea pigs fed a lithogenic diet, Lavoie et al .…”
Section: Discussionmentioning
confidence: 99%
“…A study by Xu and Shaffer [9] reported that gallbladder hypomotility was impaired by the increased bile cholesterol level. A study by Lavoie et al [63] proved that excess cholesterol in the smooth muscle of the gallbladder attenuates the ability of the muscle to contract as a result of changes in signal transduction and ion channel activity, decoupled membrane receptor-ligand interactions and disturbances in contractile protein activity. Moreover, in a subsequent study on guinea pigs fed a lithogenic diet, Lavoie et al [48] reported cholesterol accumulation in gallbladder smooth muscles in the plasma membrane, especially membrane caveolae, leading to a decrease in membrane fluidity and a subsequent change in rhythmic electric activity.…”
Section: Discussionmentioning
confidence: 99%
“…In another study using the same model, morphological changes including epithelial hyperplasia, muscularis hypertrophy and increased wall thickness were observed as early as four weeks after the mice began the lithogenic diet. These changes were accompanied by inflammatory infiltrate composed of eosinophils, macrophages, neutrophils and lymphocytes within the lamina propia [67]. Moderate granulocyte infiltrate was also observed in the gallbladder with progressive impairment of gallbladder emptying [68].…”
Section: Gallstone Disease Chronic Inflammation and Gallbladder Cancmentioning
confidence: 99%
“…Indeed, there is growing evidence that the gallbladder's ICLCs are responsible for these processes and that their function may be influenced by numerous pathological factors (e.g. cholesterol in gallstone disease) www.fhc.viamedica.pl [23]. Elucidation of the role of interstitial Cajal-like cells in the human gallbladder may contribute to new treatment options for gallbladder motility disorders, present in gallstone disease, for example.…”
Section: Discussionmentioning
confidence: 99%